2021
DOI: 10.1016/j.stemcr.2021.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression dynamics underlying cell fate emergence in 2D micropatterned human embryonic stem cell gastruloids

Abstract: Summary Human embryonic stem cells cultured in 2D micropatterns with BMP4 differentiate into a radial arrangement of germ layers and extraembryonic cells. Single-cell transcriptomes demonstrate generation of cell types transcriptionally similar to their in vivo counterparts in Carnegie stage 7 human gastrula. Time-course analyses indicate sequential differentiation, where the epiblast arises by 12 h between the prospective ectoderm in the center and the cells initiating differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
(126 reference statements)
1
22
0
Order By: Relevance
“…Specification of PGCLCs in vitro occurs within a 3D aggregate that consists of a hitherto poorly characterized fraction of somatic components. Currently, PGCLCs can be induced in various 2D aggregates but more efficiently in 3D embryoids, highlighting the importance of the structure, cell-cell interactions or signalling from adjacent tissues (Minn et al, 2020(Minn et al, , 2021). Here we have shown that these somatic cells collectively represent those in the posterior region of the embryo during gastrulation.…”
Section: Discussionmentioning
confidence: 99%
“…Specification of PGCLCs in vitro occurs within a 3D aggregate that consists of a hitherto poorly characterized fraction of somatic components. Currently, PGCLCs can be induced in various 2D aggregates but more efficiently in 3D embryoids, highlighting the importance of the structure, cell-cell interactions or signalling from adjacent tissues (Minn et al, 2020(Minn et al, , 2021). Here we have shown that these somatic cells collectively represent those in the posterior region of the embryo during gastrulation.…”
Section: Discussionmentioning
confidence: 99%
“…At the early time points of gastruloid development (0–12 h), FGF2, FGFR1, and FGFR signaling antagonists, SPRY1, DUSP6, and CBL were expressed at high levels. During differentiation (44 h) these FGF signaling components decreased, and FGF17 increased in mesoderm and endoderm along with expression of BMP, WNT, NODAL, and HIPPO signaling components (Minn et al, 2021). Comparison of mouse gastrulation and human gastruloids showed that mouse expresses high levels of Fgf8 , which is required for cell migration, while human gastruloid mesenchyme expressed high FGF17 and very low FGF8 (Minn et al, 2020).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…A human gastruloid protocol was then improved by Minn et al [14] using hES cells cultured on micropatterned surfaces of 500 µm diameter. When challenged by BMP4, cells differentiated into the three germ layers, as well as extraembryonic-like and primordial germ cells.…”
Section: Human Gastruloids To Model Birth Of Cardiac Progenitors and ...mentioning
confidence: 99%
“…They reported that these gastruloids follow the developmental kinetic of in vivo gastrulation. Epiblast and ectoderm precursors emerged after 12 h, and mesendoderm progenitors were detected by 24 h. These cells give rise to the mesoderm and endoderm by 44 h, The CS7 (Carnegie Stage 7) human gastrula [55] (featuring the same kinetic of gene expression as their in vitro counterparts [14]).…”
Section: Sound-induced Morphogenesis: a Step Forward In Cardiac Tissu...mentioning
confidence: 99%
See 1 more Smart Citation